2003
DOI: 10.1248/bpb.26.691
|View full text |Cite
|
Sign up to set email alerts
|

Antifatigue and Antistress Effect of the Hot-Water Fraction from Mycelia of Cordyceps sinensis

Abstract: Higher Basidiomycetes mushrooms have been used in folk medicine throughout the world since ancient times. Edible higher Basidiomycetes are well known for their nutritional value and acceptability as well as their pharmacological properties. Mushrooms are a nutritionally functional food and a source of physiologically beneficial and noninvective medicines. 1) Various physiological properties (pharmacological effects) such as bioregulation (immunological enhancement), maintenance of homeostasis, regulation of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 17 publications
0
35
0
2
Order By: Relevance
“…15) The recent scientific evaluation of Cordyceps sinensis has confirmed the efficacy of this extract in the treatment of cardiovascular and endocrine disorders, 16) in immune enhancement, 17) in hepatic protection, 18) in the inhibition of tumor growth, 19) and in relieving fatigue and stress. 20) Cordyceps militaris, together with Paecilomyces japonica, another entomopathogenic fungi, has been listed as a food additive in Korea since 2000, 21) and is often used in different types of tonic drinks sold in Korea due to its folkloric activities, which have not been verified scientifically. Although some recent studies have reported its effectiveness in inhibiting angiogenesis, 22) cancer cell growth, 23,24) and inflammation, 25) scientific evidences of the biological activities of Cordyceps militaris are still very limited compared to other frequently used insect-born fungi of the Cordyceps species, such as Cordyceps sinensis.…”
Section: )mentioning
confidence: 99%
“…15) The recent scientific evaluation of Cordyceps sinensis has confirmed the efficacy of this extract in the treatment of cardiovascular and endocrine disorders, 16) in immune enhancement, 17) in hepatic protection, 18) in the inhibition of tumor growth, 19) and in relieving fatigue and stress. 20) Cordyceps militaris, together with Paecilomyces japonica, another entomopathogenic fungi, has been listed as a food additive in Korea since 2000, 21) and is often used in different types of tonic drinks sold in Korea due to its folkloric activities, which have not been verified scientifically. Although some recent studies have reported its effectiveness in inhibiting angiogenesis, 22) cancer cell growth, 23,24) and inflammation, 25) scientific evidences of the biological activities of Cordyceps militaris are still very limited compared to other frequently used insect-born fungi of the Cordyceps species, such as Cordyceps sinensis.…”
Section: )mentioning
confidence: 99%
“…The forced swimming model has been used to evaluate the anti-fatigue effects of various compounds, [12][13][14][15] since this apparatus works well for evaluating the endurance capacity of mice and gives a high reproducibility. 10) BE was found to prolong the swimming time in this forced swimming test, indicating that BE possesses an anti-fatigue effect (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This apparatus was used to evaluate the endurance capacity of mice that had been administered with various compounds. [12][13][14][15] Male 5-week-old CD2F-1 mice were made to swim for 20 min at a flow rate of 6 l/min twice in one week to accustom them to swimming. We selected mice suitable for evaluating endurance capacity following the method described previously.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment of mice with C. militaris lengthens the swimming time to exhaustion (Jung et al 2004). Koh et al (2003b) reported that the hot-water extract of C. sinensis mycelia prolongs swimming endurance capacity and produces an anti-fatigue action in mice.…”
Section: Effect On Insulin Secretion and Hypoglycaemic Activitymentioning
confidence: 99%